"PENERAPAN TEORI BEHAVIORISTIK DALAM MENANAMKAN NILAI TANGGUNG JAWAB PADA SISWA SEKOLAH DASAR" - Muhammad Rizky Fauzy; Devi Fitria Sabila; Anita Yus; Yusnadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of behaviorist theory in instilling responsibility values among elementary school students. The study employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The findings indicate that behaviorist theory was implemented through habituation, stimuli, reinforcement, rewards, and educational punishments. These strategies successfully improved students’ responsibility, as reflected in their discipline in completing tasks, compliance with school rules, independent learning, and concern for the school environment. In addition to benefiting students, the implementation of behaviorist theory also assisted teachers in creating a more orderly and effective learning environment. The study concludes that behaviorist theory is an effective approach to character education because it can foster positive habits and strengthen responsibility values among elementary school students. Keywords: Behaviorist Theory, Responsibility Values, Character Education, Elementary School.